Footprints in the sand – Assessing the seasonal trends of volatile methylsiloxanes and UV-filters. (March 2019) - Capela, Daniela; Vila, Marlene; Llompart, Maria; Dagnac, Thierry; García-Jares, Carmen; Alves, Arminda; Homem, Vera
Abstract: This study focused on the determination of seven volatile methylsiloxanes (VMSs) and eleven UV-filters (UVFs) in beach sand from the Oporto's region (Portugal). A QuEChERS methodology ("Quick, Easy, Cheap, Effective, Rugged, and Safe") was used to extract VMSs from the sand, which has never been employed before. To extract the UVFs, a solid-phase microextraction (SPME) was used. The analyses were performed by gas chromatography–mass spectrometry (GC–MS). Twenty-three beach sand samples were analysed, from two campaigns – summer/winter. VMSs were found in all the samples with concentrations ranging from 0.007 ± 0.001 to 17.8 ± 0.9 ng g −1 dw, while UVFs in summer samples from 0.030 ± 0.001 to 373 ± 17 ng g −1 dw . Cyclic VMSs and octocrylene (OC) were detected in higher concentrations. In general, higher levels were detected in summer than winter. Hazard quotients were determined and 3-(4′-methylbenzylidene) camphor (4-MBC), 2-ethylhexyl 4-methoxycinnamate (EMC) and benzophenone-3 (BP3) presented values >1, which may indicate that they may pose an ecotoxicological risk. Highlights: Volatile methylsiloxanes and UV-filters determined in beach sand. Volatile methylsiloxanes were found in all samples (0.007–17.8 ng g −1 dw ). UV-filters were detected in all summer samples (0.030–373 ng g −1 dw ). In general, higher levels were detected in the summer. Three UV-filters present hazard quotients higher than 1.